Memperoleh Work Life Harmony di Tengah Tekanan Kerja: Eksplorasi Fenomenologi Kehidupan Barista di Coffee Shop Denpasar - I Gede Ardra Pratama Putra; I Putu Dharmawan Pradhana; I Nengah Wirsa; Desak Made Febri Purnama Sari (Research and Community Service UNIVERSITAS KALBIS, 2025)
The high work dynamics in the food and beverage industry place coffee shop baristas in Denpasar City under work pressure conditions that have the potential to affect work-life harmony, especially among Generation Z workers. This study aims to describe and analyze the work pressure experienced by baristas, the coping strategies used, and the role of social support and organizational policies in shaping work-life harmony. This study uses a qualitative approach with a phenomenological method. Data were obtained through observation, in-depth interviews, and documentation of informants selected purposively and snowball, including baristas, coworkers, superiors, and psychology lecturers. Data analysis was conducted thematically through coding, person statement comparison, and node comparison with the help of NVivo software. The results show that barista work pressure mainly occurs during peak operating hours, multitasking demands, and high service standards. Efforts to achieve work-life harmony are carried out through flexible time management, social support in the work environment, positive work interpretation, and organizational policies that pay attention to employee welfare. Theoretically, this research contributes to enriching the understanding of the concept of work-life harmony in the context of Generation Z by linking an individual's ability to control their behavior to the constraints of the work environment as described in Behavioral Constraint Theory. These findings are expected to serve as a practical reference for food and beverage business managers in creating a more harmonious work environment.